Ergonomic Issue in Dental Students - Monica, Grace; Handayani, Natalia Puri (Jurnal Multidisiplin Madani, 2023)
Ignoring work positions that are continuously carried out will cause musculoskeletal disorders in the future. Ergonomic positions have become a part of the dentistry curriculum. However, because the content is not directly related to dentistry, it is often ignored by the dental students. Purpose: to evaluate how much important is ergonomic position for dental students, and how the ergonomic curriculum provided can be applied in treating patients. Methods: This is a cross-sectional study by conducting a survey of 70 alumni of Undergraduate Study Program on Faculty of Dentistry who are currently undergoing a professional program at the Teaching Dental Hospital, which was obtained by accidental sampling. Respondents were asked to fill the questionnaire. Results: The ergonomic position was considered very important (48.57%), it was often forgotten (38.57%) and difficult to apply in certain cases (21.43%). 62.86% of respondents realized that the position was not appropriate when it is difficult to gain visual access. Respondents hope that ergonomics is given as often as possible in practical training and given as early as possible in dental curriculum. Conclusions: Continuing education on practical training and given as early as possible is necessary to improve the application of ergonomic positions to dental students